1988
DOI: 10.1530/jrf.0.0840469
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of post-implantation mouse embryos after maternal heat stress during meiotic maturation

Abstract: The effects of heat stress during oocyte maturation were studied in post-implantation mouse embryos. Virgin ICR mice were exposed to 35 +/- 1 degree C and 65 +/- 3% RH for 12.5 h beginning immediately after synchronization of ovulation with PMSG and hCG. Embryos of heat-stressed dams were developmentally heterogeneous and showed significant delays in development with as much as 48 h delayed development. Nearly 6% of these embryos were triploid, and another 2% were hyper-diploid. Development of triploid embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Exposure of oocytes to the room temperature, as well as to a low temperature, for as short as 1 min caused depolymerization of the spindle as reported by Aman and Parks (1994). Similarly, Baumgartner and Chrisman (1987, 1988) found that maternal heat stress caused disruption of the meiosis I spindle in maturing mouse oocytes which in turn might result in interruption of meiosis II and polar body extrusion. The mitotic spindle was found disrupted in cultured cells after HS, which resulted in chromosomal dispersion and polyploidy and ultimately the death of the cell line (Streffer 1985).…”
Section: The Effect Of Hyperthermic Conditions On the Chromatin And Tsupporting
confidence: 52%
“…Exposure of oocytes to the room temperature, as well as to a low temperature, for as short as 1 min caused depolymerization of the spindle as reported by Aman and Parks (1994). Similarly, Baumgartner and Chrisman (1987, 1988) found that maternal heat stress caused disruption of the meiosis I spindle in maturing mouse oocytes which in turn might result in interruption of meiosis II and polar body extrusion. The mitotic spindle was found disrupted in cultured cells after HS, which resulted in chromosomal dispersion and polyploidy and ultimately the death of the cell line (Streffer 1985).…”
Section: The Effect Of Hyperthermic Conditions On the Chromatin And Tsupporting
confidence: 52%
“…Many in vitro and in vivo studies have examined the effects of heat stress on maturation and developmental competence of oocytes. Exposing females to heat stress after fertilization caused decreases in the quality and quantity of embryos in cows after superovulation [69,70] and mice [71][72][73][74][75], and caused decreases in fetal growth in pigs [67], mice [74] and beef cows [76]. In vitro studies also revealed the effect of heat stress on oocyte maturation.…”
Section: Effects Of Heat Stress On Oocyte Growth Fertilization and Ementioning
confidence: 99%
“…The oocyte remains susceptible to heat stress through the preovulatory period. As shown in cows (Putney et al 1989) and mice (Baumgartner & Chrisman 1988;Aroyo et al 2007;Roth et al 2008), experimental heat stress coincident with ovulation and oocyte maturation may or may not have an effect on the capacity of oocytes to be fertilized but the resultant embryos are more likely to develop slowly or abnormally. Damage to the oocyte during the preovulatory period could reflect hormonal perturbations.…”
Section: The Female (A)mentioning
confidence: 99%